2017
DOI: 10.1177/0013124517713604
|View full text |Cite
|
Sign up to set email alerts
|

“Good Intentions Can Only Get You So Far”: Critical Reflections From Teach For America Corps Members Placed in Special Education

Abstract: Research on Teach For America (TFA) continues to grow, but scant scholarship has explored the experiences of its corps members working in special education in urban schools. As teachers who require in-depth knowledge of legal and liability processes as well as effective pedagogical practices, corps members in special education positions have significant demands placed on them that often lie beyond the roles and responsibilities of other TFA teachers. This article therefore focuses on the experiences of five TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…While additional findings from the broader study can be found elsewhere Thomas, 2017Thomas, , 2018, the findings presented in this article stem from CM responses to three specific interview questions focused on the development of teacher professional identity. Each CM was asked the following: a) How does it feel to call yourself a teacher?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While additional findings from the broader study can be found elsewhere Thomas, 2017Thomas, , 2018, the findings presented in this article stem from CM responses to three specific interview questions focused on the development of teacher professional identity. Each CM was asked the following: a) How does it feel to call yourself a teacher?…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none of these three characteristics may hold true for CMs, who are often teaching beyond the realm of their undergraduate education, and undergo only basic 'training' in what Beijaard et al would regard as pedagogical and didactic knowledge in their Summer Institute. Thomas (2017) illustrates the potential for this disconnect, highlighting how "an accounting major who co-teaches sixth grade math during a 5-week Summer Institute does not have requisite background knowledge of approaches and processes to begin a placement in Grades 7 to 12 special education" (p. 17). Indeed, given this trajectory, it would be challenging for most to see themselves as experts.…”
Section: Tfa and Teacher Identitymentioning
confidence: 99%
“…In a recent qualitative study of five special education teachers at TFA, Thomas (2018a) found that the teachers perceived a lack of explicit support from TFA staff members and insufficient training in special education procedures. Although TFA launched an initiative focused on developing special educators in 2015, participants reported that they received little specialized training, and that the TFA employees who trained them were often from a different state or novice teachers themselves.…”
Section: Methodsmentioning
confidence: 99%
“…What would that knowledge add up to in terms of methodology, theory and practice in relation to Bangladesh, but also to globalization? These questions gained traction particularly because similar studies with a specific focus on philanthrocapitalism and education policy have been conducted mostly in the developed world contexts (see Au and Ferrare, 2015;Elliott, 2018;Friedrich, 2014;Friedrich et al, 2015;Labaree, 2010;Lefebvre and Thomas, 2017;Smart et al, 2009;Straubhaar and Friedrich, 2015;Yin et al, 2019;Thomas, 2018bThomas, , 2018a. This body of literature, however, provided practical insights into how TFAll has materialized, particularly in its host countries, with prototypical idiosyncrasies.…”
Section: Introductionmentioning
confidence: 99%